The trade impact of European union preferential policies an analysis through gravity models - De Benedictis, Luca; Salvatici, Luca (Springer Berlin Heidelberg Imprint: Springer, 2011)
The book investigates the EU preferential trade policy and, in particular, the impact it had on trade flows from developing countries. It shows that the capability of the "trade as aid" model to deliver its expected benefits to these countries crucially differs between preferential schemes and sectors. The book takes an eclectic but rigorous  approach to the econometric analysis by combining different specifications of the gravity model. An in-depth presentation of the gravity model is also included, providing significant insights into the distinctive features of this technique and its state-of-art implementation. The evidence produced in the book is extensively applied to the analysis of the EU preferential policies with substantial suggestions for future improvement. Additional electronic material can be found onli